Un mandat représentatif peut en cacher un autre : lumière sur l’administration parlementaire sous la Cinquième République - Mohesh Balnath (Cahiers Jean Moulin)
Political theorists have long deemed representative mandates at the national level to be the prerogative of members of Parliament. The Fifth Republic in France may very well give institutional foundations to the idea that administrative bodies, mainly the one assisting members of Parliament, also hold representative mandates.